THE EQUATORIAL COORDINATES AND B-MAGNITUDES OF THE STARS IN THE SOUTHERN HEMISPHERE ZONES BASED ON THE DIGITIZED ASTRONEGATIVES OF FON PROJECT AT THE ULUGH BEG ASTRONOMICAL INSTITUTE - Yuldoshev, Q. X.; Muminov, M. M.; Ehgamberdiev, Sh. A.; Usmanov, O. U.; Relke, H.; Protsyuk, Yu. I.; Kovylianska, O. E.; Protsyuk, S. V.; Andruk, V. N. (Одеські астрономічні публікації, 2016)
FON (Russian abbreviation of the Photographic Sky Survey) were carried out at 6 observatories. The Kitab Observatory (KO) of Ulugh Beg Astronomical Institute (UBAI) of theUzbekAcademyof Sciences (UzAS) was involved in this project from 1981 to 1996. For the observations the Double Astrograph of Zeiss (DAZ, D/F = 40/300, 69"/mm) was used. On the FON project about 2600 photographic plates were exposed. In October, 2015 digitization of these astroplates were started using EPSON Expression 10000XL flatbed scanner with the spatial resolution of 1200 dpi and completed in June, 2016. The first stage of the work is the processing of the 2000 photographic plates in zones of the southern hemisphere with the declination between 0 and -20 degrees. The 1704 plates have already been processed. The equatorial coordinates α, δ of stars and galaxies were determined in the system of the Tycho2 catalogue and the Bmagnitudes in the system of the photoelectric standards. UBAI UzAS,Tashkent(Uzbekistan), ASU, Andijan (Uzbekistan), WHO,Essen(Germany), RI NAO, Nikolaev (Ukraine), MAO NASU, Kyiv (Ukraine) have taken part in the processing of the digitized images. For the data reduction the MIDAS package and software, developed in the MAO NASU were used. Based on the results of the processing of the astronegatives in the sectors of right ascension from 0 hours to 24 hours and declination from - 20° to 0° the internal errors of the catalogue were estimated. The errors calculated for all stars are 0.17" and 0.18m respectively. For the stars brighter than 14 magnitude the errors are 0.08" and 0.07m for the equatorial coordinates and B-magnitudes respectively.